Metabolic pathway monitoring of phenalinolactone biosynthesis from Streptomyces sp. Tü6071 by liquid chromatography/mass spectrometry coupling. (22nd May 2014) - Kiske, Christiane; Erxleben, Anika; Lucas, Xavier; Willmann, Lucas; Klementz, Dennis; Günther, Stefan; Römer, Winfried; Kammerer, Bernd
<x xml:space="preserve">Abstract</x> RATIONALE A rapid and precise analytical method for the investigation of natural products is required for pathway monitoring of the biosynthesis of secondary metabolites. Phenalinolactones, used in antibiotic research, are produced by Streptomyces sp. Tü6071. For the analysis of those compounds, prior to mass spectrometric analysis, an efficient separation technique is required. METHODS For the identification of phenalinolactones from liquid cultures of Streptomyces sp. Tü6071, a new method comprising the combination of solid‐phase extraction (SPE) prior to liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI‐MS/MS) was established. MS/MS product ion scans were applied for phenalinolactone detection and structure elucidation, performed in negative mode and optimized for sensitivity and specificity. For the discovery of new intermediates, a MS/MS precursor ion scan was applied. RESULTS Analysis of the extracts revealed that the Oasis® MAX cartridge, containing a quaternary amine functionality, is the most efficient SPE material for purification of phenalinolactones, since it allowed sufficient enrichment and detection of intermediates from the biosynthetic pathway by LC/ESI‐MS/MS. Using the precursor ion scan technique, two new secondary metabolites, PL IM1 with m/z 672.6 and PL IM2 with m/z 433.3, have been detected. The structures of the new intermediates are postulated and arranged into the biosynthetic pathway of phenalinolactones. CONCLUSIONS A precise analytical method was established for the identification of phenalinolactones by combining purification from Streptomyces using SPE prior to LC/ESI‐MS/MS. By optimising LC/ESI‐MS/MS settings, this method has been successfully applied for pathway monitoring of secondary metabolites. Application of a precursor ion scan allowed for the identification of unknown intermediates in biosynthetic pathways. Copyright © 2014 John Wiley & Sons, Ltd.